Generating non-normal distributions for interval schedules : effects on instrumental behavior - Albayrak, Emirhan Buğra. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2023., 2023)
VI schedules are used in instrumental conditioning to obtain a relatively con stant response rate. In VI schedules, a reward is delivered following an operant re sponse, that is emitted after a variable time interval has passed. A peculiarity of VI schedules is that responding increases as time spent in an interval increases, producing output which is less uniform. To reduce this effect, positively skewed distributions have been implemented. However, non-normal distributions cannot be generated with cur rent number generators. Here, we have established a procedure in Microsoft Excel that generates non- normal distributions. We further ran instrumental conditioning proto cols utilizing the distributions we generated to see the effects on instrumental behavior. We hypothesized that our distributions will lead to a time independent behavior after discrimination training, in which animals learned to discriminate between existence of the stimulus and a no- stimulus context. First, we analyzed discrimination training by comparing lever press rates and lever press latencies across days of training and time within session. Then, to see how our distributions affected the time-dependency, we analyzed the relationship between time after stimulus onset and lever press rates during discrimination training performing correlation analyses. We found that the an imals pressed the lever less in the 21 st day of discrimination training in EXT state compared to the 1 st day. We also found that, although there was a significant moder ate correlation between time after stimulus and the lever press rate in the 1 st day of discrimination training, the correlation was not significant for the 21 st day. However, a curvilinear function explained over 70% of the variance in the data. Here we showed an easy-to-use method to generate non-normal distributions with Microsoft Excel. Our findings suggest that distributions generated by the given formula led to learning in rats in 21 days, but the lever press responses were not time independent contrary to our expectations. NOTE Keywords : Instrumental Conditioning, Variable Interval Schedules, Discrimination Training, Non-normal Distributions.
Keywords: Operant conditioning.